Mobile Intention Recognition - Kiefer, Peter; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
none
Introduction -- Mobile Intention Recognition -- Related Approaches in Plan Recognition -- Mobile Intention Recognition with Spatially Constrained Grammars -- Evaluation and Discussion -- Conclusion and Outlook.
Keywords: Computer science; Computer Communication Networks; Artificial intelligence; Computer simulation; Optical pattern recognition; Algorithms; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Algorithms; Simulation and Modeling